Intersections of Sport and Society in Creative Writing - McGowan, Lee.; Symons, Kasey (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited collection is positioned at the nexus of sports, society and creative writing. In its explorations of the intersections of sports writing, analysis of literary contributions and examinations of craft, it offers rare consideration of a rich diversity of form in narratives that occur in, and as creative practice. Included in the collection are dynamic academic investigations into football writing and poetry focused on community sporting activities in Afghanistan, to those addressing the intersections of writing and boxing in the reflexive reclamation of the post-trauma self, the absence of women in the rodeo and who and what is represented in our sports shelves. This book breaks new ground in approaches to sport's role in creative writing and what creative writing can provide in furthering our understanding of sport in society. The works in this edited book draw on a diverse range of methods to interrogate the processes, concepts and liminal spaces through an intersectional array of voices, offering analysis and insight into the application of creative writing knowledge and practice in relation to sport and its impact on wider discipline discussion and research. It is relevant to students and scholars studying and researching creative writing, sports writing, sports studies, cultural studies and sports media studies.
Beyond the Box Score: Reflecting on the Intersections of Sport and Society in Creative Writing -- Sport and Society in Creative Writing: Tradition as Platform of Expectation -- Sportshelfie: Representation in the Sport Section of Australian Bookshops and Libraries -- Don Davies & Hugh Mcilvanney: The Literary Football Reporters who Elevated British Sports Journalism -- Notes on a Scandal: Lemon and Haigh on Australian Cricket's 'Sandpapergate' -- Sport and Society in Creative Writing: Place in Sports Fiction -- The Architecture of the Sporting Site in Irish Fiction -- Fury and Failure in Spanish Football Stories of the 1960s -- "Air This Thin Turns Anyone into a Mystic": Extreme Sport as Metaphor for Societal Disengagement in Steven Heighton's Every Lost Country (2010) -- Sport and Society in Creative Writing: Intersections with Practice -- Write and Write It Again: Using Reflective Autoethnography and Practice-Led Creative Writing to Create New Narratives of Women in Sport -- The Queen and the Clown: A Poetic Inquiry into Women's Roles In Rodeo -- Gesturing Towards Decolonial Openings: Sports and Poetry -- Reclaiming the Borderlands -- Creative Writing Tools in the Exploration of Intersections of Sport and Society -- Left Write Hook: 'Boxing with the Boys' -- Autoethnography and Driving Change.
Keywords: Creative writing; Communication in sports; Literature; Communication; Sports sciences; Creative Writing; Sports Communication; Literature; Media and Communication; Sport Theory